FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN BIDAN PRAKTEK MANDIRI ERA JAMINAN KESEHATAN NASIONAL DI KOTA SEMARANG - Maynisa Puspita Kusuma Wardani; Ayun Sriatmi; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
BPJS Kesehatan have to maintain quality control and cost control. Therefore, the performance of primary health care provider has to be comply with medical procedure which in theoritical, it stated that individual performances were affected by individual job satisfications. There were any complaintsa about responsibility and right among private midwives who already made connection with family doctor. Therefore, the research about the satisfication of private midwives is important to determine factors related of the satisfication of private midwives in the era of national health insurance in Semarang. The method of this research was using Explanatory Research with Cross Sectional approach. The population in this research was 88 peoples with 62 peoples as sample research. The analysis of the data was using univariate and bivariate analysis with Rank Spearman Test. The results of the univariate analysis on job satisfaction percentage of dissatisfied 80.6% and statisfied is 19.4% . Responsibility the percentage of the low responsibility is 46.8% but the high responsibility is 53.2% . The percentage of assessment the substitutionof claim tariff which not timely 74.2% and 25.8% on-time ratings. The bad relationship between personal family doctor and private midwife 40.3% but good relationship 59.7%. Assessment of bad proceduresis 40.3%, 59.7% good procedure. Results showed that there were relationship between responsibility (p-value 0,000), the substitution of claim tariff by BPJS that usual based on ontime aspect (p-value 0,003), the relationship between individual with family doctor connection and among midwives(p-value 0,000), and the administration prosedure according to claim changing in BPJS(p-value 0,041) with job satisfication of private midwives in the ere of national health insurance in Semarang so that efforts should be made to improve the satisfaction of private midwives according the rules.